Mini-Review: Regenerating the Corneal Epithelium With Simple Limbal Epithelial Transplantation - Singh, Aastha; Sangwan, Virender S. (Frontiers in Medicine, 2021)
Simple limbal epithelial transplantation (SLET) is an ingenious, low cost and effective technique of limbal stem cell transplantation (LSCT) that is increasingly being taken into practice across the world. Since it was first described a decade ago, the technique has been performed in a variety of cases of limbal stem cell deficiency (LSCD) and has undergone several innovative modifications. Published literature on SLET has progressively increased over time and successful outcomes in various clinical scenarios have been reported. This concise review attempts to present a crisp account of SLET covering the indications and contraindications of performing the procedure; a detailed account of pre-operative workup and preparation; surgical technique and its modifications; post-operative course, care, and possible complications as well as published outcomes of surgery from across the world. Comparative analysis of various techniques of LSCT have been discussed and common concerns of surgeons practicing or those who are planning to start practicing SLET have been addressed. The authors hope that the pragmatic insights and pearls given at the end of the review will aid the surgeons in performing this technique to provide maximum benefit to patients suffering from the potentially blinding condition of LSCD.